Stress distribution and mechanical response of PCCP with broken wires. (15th October 2021) - Zhai, Kejie; Guo, Chengchao; Fang, Hongyuan; Li, Bin; Ma, Baosong; Hu, Qunfang; Wang, Fuming
Highlights: A theoretical model for calculating the stress distribution of steel wire is proposed. The theoretical model is evaluated by comparing the shrinkage value from an experiment on a PCCP with broken wires. A three-dimensional finite element model of PCCP is also established, and the stress–strain responses are assessed against the experimental and theoretical models. The threshold of wire breakage ratio is 4.8%, 11.7% and 11.4% for PCCP with an inside diameter of 1, 400 mm, 2, 000 mm and 2, 800 mm, respectively. Abstract: Wire breakage in prestressed concrete cylinder pipe (PCCP) is the most common type of damage. A theoretical model for calculating the stress distribution of steel wire is proposed, by assuming a linear distributed pattern of bond stress. The theoretical model is evaluated by comparing the shrinkage value from an experiment on a PCCP with broken wires. A three-dimensional finite element model of PCCP is also established, and the stress–strain responses are assessed against the experimental and theoretical models. Upon the successful calibration of the numerical model, a parametric investigation is conducted on the mechanical responses of PCCP with different wire breakage ratio, from which the thresholds of wire breakage ratio for PCCP are established. The bearing capacity of PCCP decreases with the increase of wire breakage ratio, but the decreasing trend slows down. The threshold of wire breakage ratio is 4.8%, 11.7% and 11.4% for PCCP with an inside diameter of 1, 400 mm, 2, 000 mm and 2, 800 mm, respectively; whereas the threshold is determined as 4.7%, 4.7%, 4.8%, 5.3% and 6.2% for PCCP with an area of steel wire of 1598 mm 2 /m, 1317 mm 2 /m, 1088 mm 2 /m, 910 mm 2 /m, and 878 mm 2 /m, respectively.